Tense Logics and Determinism - Surowik Dariusz (Studies in Logic, Grammar and Rhetoric)
In this article, we will discuss the concept of logical determinism and arguments in favor of determinism based on the law of excluded middle and the principle of causality. We will also discuss minimal tense logic and tense logic of branched time, constructed to reject the thesis of logical determinism.